Evaluation Status Hara Land and Leaf Plant Coconut Palm oil (Elaeis guineensis) Plantation People in Linggabayu District, Mandailing Natal Regency, North Sumatra Province, Indonesia - Noviantika Nasution; Mukhlis; Mariani Br Sembiring (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2026)
Oil palm (Elaeis guineensis Jacq.) is one of the most important plantation crops in Indonesia, and requireseffective soil and nutrient management to achieve optimal productivity. This survey aimed to evaluate soil andleaf nutrient status in oil palm plantations managed by smallholders in Linggabayu District, Mandailing NatalRegency, North Sumatra Province, Indonesia. Data were collected through field observations and soil and leafsampling in Batuloting Village, Banjar Selamat, and Padang Silojongan, with 10 trees sampled at each location. Allsamples were analyzed at the PT Socfin Indonesia (SOCFINDO) Laboratory to determine the macronutrient contentof nitrogen (N), phosphorus (P), potassium (K), and magnesium (Mg). The results showed that soil N, P, and Klevels at most locations were low to very low, while Mg levels ranged from low to high. Leaf tissue analysisrevealed that nitrogen content was generally within the optimal range at almost all locations, except in BanjarSelamat Village and Padang Silojongan, where deficiency symptoms were observed. Phosphorus content in leavesranged from adequate to optimal, while potassium content varied from low to optimal across sampling locations.Magnesium levels in leaves were relatively adequate, although a small percentage of samples still indicateddeficiencies. These findings suggest that, despite generally limited soil fertility, oil palm plants can effectivelyabsorb nutrients. This condition is supported by current fertilization practices and the physiological adaptabilityof oil palm plants to efficiently utilize soil nutrients. Therefore, site-specific nutrient management, particularlyfor N, P, and K, is recommended to improve soil fertility and maintain oil palm productivity in smallholderplantations.